The Dilemma of Regularly Missed Diagnoses: ADTKD - Knaup, Karl X.; Büttner-Herold, Maike; Popp, Bernt; Stoeckert, Johanna; Schiffer, Mario; Schueler, Markus; Reis, André; Amann, Kerstin; Ekici, Arif B.; Wiesener, Michael S (Archives of Clinical and Medical Case Reports, 2019)
An ill-defined number of patients with chronic kidney disease (CKD) receive an incorrect diagnosis. Numerous diseases are rather unspecific in terms of clinical appearance and histological characteristics, particularly hereditary kidney diseases. Autosomal dominant tubulointerstitial kidney diseases (ADTKD) can be seen as a paradigm of the diagnostic challenge, where only molecular genetics can assure the diagnosis. We report a young lady with CKD who historically received a diagnosis of “biopsy-proven” IgA nephropathy (IgAN). She received 8 months of oral steroids, with side effects but further renal deterioration. Despite a positive family history with CKD over at least three generations, this clue was not considered. We established a doubtless diagnosis of MUC1-associated ADTKD by a heterozygous frameshift-causing mutation by SNaPshot minisequencing in our index patient and her affected father. Furthermore, the mucin 1 frameshift protein was readily detectable in the 10 year old kidney biopsy. We hypothesize that similar diagnostic failures are frequent in the current routine. Interestingly, the misdiagnosis of IgAN may be an underestimated problem since a substantial fraction of the healthy population may show mesangial proliferation and IgA deposition. The correct diagnosis of hereditary diseases has several clinical implications and should be the ultimate aim of precision nephrology.